Logic, methodology and philosophy of science IV : proceedings of the Fourth International congress for Logic, Methodology and Philosophy of Science, Bucharest, 1971 - Suppes, Patrick, 1922-2014 (Studies in logic and the foundations of mathematics, 1973)
Provability, Computability and Reflection.